Optical-Quantum Security using Dark-Bright Soliton Conversion in a Ring Resonator System - S. Tunsiri; S. Kanthavong; None Louangvilay; S. Mitatha; P.P. Yupapin (My University, 2012)
We present a new concept of quantum cryptography using dark-bright soliton conversion behaviors within a nonlinear ring resonator, in which the orthogonal soliton is established among the soliton conversion. A new model of add/drop filters is modified which is known as a PANDA Ring resonator is proposed. The entangled soliton(photon) can work in the same way of the entangled photon, but in this case the entangle soliton is gained more power that give the advantage of long distance quantum communication. In application, the high capacity quantum communication is also variable by using the multivariable entangled solitons.
Keywords: Photon entanglement; Advanced Fiber Laser Technologies